Electromagnetic Modeling of Active Circuit using Wave Concept Iterative Process - Amri Houda; Zaabat Mourad (Bulletin of Electrical Engineering and Informatics, 2016)
The wave concept iterative process is a procedure used for analyses planar circuits, this method consists in generating a recursive relationship between a wave source and reflected waves from the discontinuity plane which is divided into cells. A high computational speed has been achieved by using Fast Modal Transform (FMT). In this paper we study a patch antenna and MESFET transistor, to determine the electromagnetic characteristics of these structures.